SRABAD DALAM SENI RUPA TRADISI CIREBON - Suryawan . (Saraswati)
Traditional art has a characteristic, namely the art devoted for religious interests. Thus art, religion, and society become unity. Traditional culture the people of Cirebon much influenced by the culture of Sundanese, Javanese, Hindu, Chinese, and Islam. Cultural influences are then visualized by the symbols guide each culture, which disguise one another as well as forming a whole. One of the culture result is srabad that is the result of creative ideas as a compromise measure from the view of some people was believe about the restriction of drawing living being as a whole. In the development of srabads themes then influenced the development of Cirebons art tradition.This research was the study of the existence srabad which indicated the strength of the relationship of art and spiritual forms. This study was also a means of identified the influence of culture, explorated of the meaning and characteristics srabad. To achieved these objectives, this study used qualitative research, used the descriptive method, by took a sample of srabad. Data was collected through observation, study of literature, interviews and documentation. Data analysis was conducted by collecting and reviewing all existing data. Examination of the validity of the data was done by triangulation.The results showed that, first, the culture of Sundanese, Javanese, Chinese and Islamic art traditions greatly influence Cirebons art; second, srabad is the result of a spiritual conception of society of Cirebon, in its communication to the self, God, and nature; Third, traditional art of Cirebon including srabad, created and held with in the frame work of religious needs, beside as the spectacle is also as the guidance, will shift its meaning if interpret not as a whole.Keywords: Srabad, Fine art tradition, Cirebon